2021
DOI: 10.1007/s10096-021-04282-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus detection in ovarian cancer: a meta-analysis

Abstract: We conducted a meta-analysis of published data to update and estimate the prevalence of HPV in ovarian cancer. A comprehensive literature search was performed according to the PRISMA guidelines. Eligible articles published from 1989 until 2020 by searching Web of Sciences, Pubmed, Embase, and the Cochrane Library Central databases were gathered. A pooled estimation of HPV prevalence with a 95% confidence interval (CI) was calculated based on a random effect model. Quantitative assessment of heterogeneity was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
(131 reference statements)
2
12
0
Order By: Relevance
“…Transcriptionally active HR‐HPV was strongly associated with Barrett's dysplasia and esophageal adenocarcinoma 36 . In other cancer types, for example, the association of HR‐HPV with ovarian cancer is not strong 37 . In a case report, 3 ovarian tumors that metastasized from CC showed the same HPV genotype (HPV18) and the same integration site from its primary endocervical adenocarcinoma 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptionally active HR‐HPV was strongly associated with Barrett's dysplasia and esophageal adenocarcinoma 36 . In other cancer types, for example, the association of HR‐HPV with ovarian cancer is not strong 37 . In a case report, 3 ovarian tumors that metastasized from CC showed the same HPV genotype (HPV18) and the same integration site from its primary endocervical adenocarcinoma 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Other viral types, including HPV33, HPV6, and HPV45, as well as mixed HPV infections were also reported [6,246,247,253,258]. Two meta-analyses, published in 2013 and 2021, demonstrated that the pooled HPV prevalence in OC tissue worldwide was approximately 16%, but wide geographical variation (from 0% to 81%) was found [261,262]. The highest pool prevalence of HPV in OC cases was reported in Asia (45.6% and 30.9%) and Eastern Europe (18.5% and 29.3%), the lowest-in North America (0%) [261,262], respectively.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Two meta-analyses, published in 2013 and 2021, demonstrated that the pooled HPV prevalence in OC tissue worldwide was approximately 16%, but wide geographical variation (from 0% to 81%) was found [261,262]. The highest pool prevalence of HPV in OC cases was reported in Asia (45.6% and 30.9%) and Eastern Europe (18.5% and 29.3%), the lowest-in North America (0%) [261,262], respectively. Our study showed the presence of HPV DNA, mostly the HPV16 type, in the majority of cancerous ovarian tissues [6].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…The role of viruses, such as human papillomavirus, in the initiation, promotion, and progression of OvCa is unknown ( Ibragimova et al, 2021 ). With the use of highly sensitive techniques, several groups have detected the presence of a viral genome in OvCa tissues ( Pathak et al, 2020 ), but it is not sufficient to prove that viruses are a causal factor in the genesis of the disease ( Cherif et al, 2021 ).…”
Section: Inflammaging Hypotheses Of Ovarian Cancer ( Fig 1 ...mentioning
confidence: 99%